Mid‐term outcome in patients with bicuspid aortic valve stenosis following transcatheter aortic valve replacement with a current generation device: A multicenter study. Issue 6 (4th September 2019) - Attinger‐Toller, Adrian; Bhindi, Rahul; Perlman, Gidon Y.; Murdoch, Dale; Weir‐McCall, Jonathan; Blanke, Philipp; Barbanti, Marco; Sathananthan, Janarthanan; Ruile, Philipp; Gandolfo, Caterina; Saia, Francesco; Nietlispach, Fabian; et al.
Abstract: Objectives: To perform clinical and echocardiographic follow‐up beyond 1 year in consecutive patients with severe bicuspid aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR) with a current generation balloon‐expandable valve. Background: Treatment of bicuspid aortic valve disease with TAVR remains controversial and late follow‐up data is still scarce. Methods: We collected baseline characteristics, procedural data, 30‐day and mid‐term clinical follow‐up findings from six centers in Europe and Canada from patients with bicuspid AS treated with TAVR using the SAPIEN 3 valve. Results: Seventy‐nine patients underwent TAVR. Mean age was 76 ± 9 years; median STS risk score for mortality was 3.8% (interquartile range 2.3–5.5%). Median follow‐up was 390 days (interquartile range 138–739 days). Device success was achieved in 95% of patients. Postimplantation mean aortic gradient decreased from 50.2 ± 16.2 to 8.8 ± 4.4 mmHg and no patient had more than mild aortic regurgitation. At last follow‐up, there was persistent good valve performance. At 30 days and 1 year, the rates of all‐cause mortality were 3.8 and 7.7%, stroke 1.2 and 1.2%, and the rate of new pacemakers 18 and 18%. Conclusions: Our data confirm that treating patients with stenotic bicuspid aortic valves is safe, effective, and has favorable valve performance over time.